Mapping the Global Landscape of Project-Based Learning in Higher Education: A Bibliometric Analysis (2015-2025) - Fattah, Fuad Abdul; Pratomo, Laurensia Claudia; Rusmana, Dede; Sari, Prima Ratna; Muhammad, Naufal Dzakwana (LPPM Institut Pendidikan Nusantara Global, 2025)
This study maps the global research landscape of Project-Based Learning (PjBL) in higher education from 2015 to 2025 using bibliometric analysis of 318 articles from 198 journals indexed in Scopus. The findings indicate steady publication growth (1,06% annually), with Spain, Indonesia, and the United States as the leading contributors. Core journals include Sustainability, Education Sciences, and Frontiers in Education, reflecting strong connections between PjBL, sustainability, pedagogy, and digital innovation. Thematic analysis reveals PjBL is primarily implemented in social sciences, STEM, and engineering disciplines, while its application in entrepreneurship and the arts remains limited. Although the topic has reached bibliometric maturity, implementation challenges persist especially in developing countries due to infrastructural and pedagogical constraints.